Արիստակէս վարդապետ Լաստիվերցու գեղագիտական հայացքները՝ ըստ նրա «Պատմութեան» - Վարդանեան, Լուսինէ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
История историка XI века Аристакэса Ластивертци создавалась по правилам средневековой христианской эстетики, что отражалось в трактовках историком действительности, характеристиках действующих лиц, размышлениях историка о грехе и искуплении. Средневековье последовательно отстаивало представление о мире как сотворении Творца. Это творение не могло быть несовершенным, ибо то, что стало несовершенным из-за человеческих грехов, должно было быть исправлено, чтобы восстановить изначальное совершенство. Подобно своему гениальному предшественнику Григору Нарекаци, архимандрит Аристакэс говорит от общего имени (в данном случае армянского народа), поэтому он и воспринимает мир во всей его полноте. Идеалом че-ловека в характеристике Аристакэса Ластивертци является интеллектуальная система Средневековья. самостоятельность его возрождения неприемлема для историка. Эстетические категории прекрасного, возвышенного,добра, света и цвета имеют уникальное применение в сочинении Аристакэса Ластивертци, но особое значение имеет категория патриотизма, которая при необходимости отклоняется даже от требования доброты и смирения христианского учения. The “History” of the 11th century historian Aristakes Lastivertsi was created according to the rules of medieval Christian aesthetics, which was reflected in the historian’s interpretations of reality, descriptions of the acting characters, and thoughts about sin and atonement. The Middle Ages consistently upheld the view of the world as the creation of the Creator. That creation could not be imperfect, so what had become imperfect because of human sins had to be corrected in order to restore the original perfection. Like Gregory of Narek, his brilliant predecessor, Archimandrite Aristakes speaks on behalf of the whole (in this case, the Armenian nation); therefore, he also perceives the world in its entirety. The ideal of man in the characteristics of Aristakes Lastivertsi can be found in the intellectual system of the Middle Ages: the independence of its revival is unacceptable for the historian. The aesthetic categories of beautiful, noble, good, light and color have unique usages in the work of Aristakes Lastivertsi, but of particular importance is the category of patriotism, which, if necessary, deviates even from the requirements of kindness and humility of the Christian faith.
Keywords: Պատմաբանասիրութիւն